Advancing non-small cell lung cancer treatment: the power of combination immunotherapies - Wu, Yuanlin; Yu, Guangmao; Jin, Ketao; Qian, Jun (Frontiers in Immunology, 2024)
Non-small cell lung cancer (NSCLC) remains an unsolved challenge in oncology, signifying a substantial global health burden. While considerable progress has been made in recent years through the emergence of immunotherapy modalities, such as immune checkpoint inhibitors (ICIs), monotherapies often yield limited clinical outcomes. The rationale behind combining various immunotherapeutic or other anti-cancer agents, the mechanistic underpinnings, and the clinical evidence supporting their utilization is crucial in NSCLC therapy. Regarding the synergistic potential of combination immunotherapies, this study aims to provide insights to help the landscape of NSCLC treatment and improve clinical outcomes. In addition, this review article discusses the challenges and considerations of combination regimens, including toxicity management and patient selection.